THE USE OF CARTOON “FROZEN” MOVIE AS VISUAL MEDIA TO IMPROVE THE STUDENTS’ ABILITY IN LEARNING SPEAKING: A CASE OF NINTH GRADE STUDENTS OF SMP SULTAN AGUNG 1 SEMARANG - Dyah Nugrahani; Fitria Fitria (Universitas PGRI Semarang, 2013)
The objectives of this study are (1) to find out the speaking ability of students in grade 9th of SMP SultanAgung 1 taught without using Cartoon “frozen” movie. (2) to find out the speaking ability of students in grade 9th of SMP Sultan Agung 1 taught with cartoon “frozen” movie. (3) to know the difference in speaking ability of students in grade 9thin SMP Sultan Agung 1 taught with and without using cartoon “frozen” as Media.This study investigates the speaking ability of the students taught using cartoon “frozen” movie as media, the speaking ability of the students taught without using cartoon “frozen” movie as media, whether or not there is significant difference of speaking ability between the students taught using cartoon “frozen” movie and those taught without cartoon “frozen” as media..This study, belongs to experimental quantitative method. The population of the study was ninth grade students of SMP Sultan Agung 1 Semarang. In this study, purposive sampling has been used to take the samples. The samples were 9A as experimental group, and 9E as control group. Then, the instruments of this study were test and document.It was found that the mean of experimental group was 72.53. Meanwhile, the mean of control group was 60.67. The mean of experimental group was higher than the mean of control group. So, it found that there was significant difference of the speaking ability between the students taught using cartoon “frozen” movie and those taught without using cartoon “frozen” movie as media.From the research findings, it can be concluded that since the use of cartoon “frozen” movie as modelin teaching speaking , the students were more interested in teaching learning process. It was proven based on the computation. The result of t-test was3.71 and t-table was 2.00. So the value of t-test was higher than t-table (3.71>2.00).It concludes that using cartoon “frozen” movie as media can promote students speaking ability. Based on the conclusion, some suggestions were proposed for the teacher and the students. The teacher can use cartoon “frozen” movie as media for teaching speaking. The students can use cartoon “frozen” movie to enhance the understanding of the content information, and to promote their speaking ability.